Phase transitions of the second order - Yukhnovskii, I.R (World Scientific, 1987)
Translated from the Russian by A.Y. Saban & S. N. Voitiuk; Translation of: Fazovye perekhody vtorogo roda; Bibliography: p. 321-327; Quỹ Châu Á